Frederic Franklin a biography of the ballet star - Norton, Leslie 1952-; Franklin, Frederic 1914- (McFarland, 2007)
"This biography covers his entire career. Each chapter covers a different period of Franklin's life, including the peak of his performing career as a principal dancer with the Ballet Russes de Monte Carlo, his legendary professional partnership with Alexandra Danilova, and his role in introducing ballet to millions of Americans during World War II"--Provided by publisher.
"This biography covers his entire career. Each chapter covers a different period of Franklin's life, including the peak of his performing career as a principal dancer with the Ballet Russes de Monte Carlo, his legendary professional partnership with Alexandra Danilova, and his role in introducing ballet to millions of Americans during World War II"--Provided by publisher.
Includes bibliographical references and index
Keywords: Franklin, Frederic -- 1914-; Ballet Russe de Monte Carlo -- History; Geschichte; Ballet dancers -- Biography; Ballet; Biografie; Fiktionale Darstellung